Synthesis and catalytic application of new [IrCl(cod)2(μ2-diNHC)] and [Ir(cod)(sulfonated phosphine)2(μ2-diNHC)] complexes. (22nd June 2022) - Orosz, Krisztina; Czégéni, Csilla Enikő; Udvardy, Antal; Papp, Gábor; Marozsán, Natália; Kathó, Ágnes; Joó, Ferenc; Horváth, Henrietta
Abstract: Four new dinuclear iridium(I) complexes were synthesized from the di(N-heterocyclic carbene) ligand precursors 1, 1′-methylene-bis(3-benzyl-imidazolium)dichloride and 1, 1′-methylene-bis(3-(2, 4, 6-trimethylbenzyl)imidazolium)dichloride. The complexes were fully characterized by spectroscopic methods, HR-MS (ESI) spectrometry, furthermore, the structure of complexes 1 and 2 were determined by single-crystal X-ray diffraction. Complexes 3a and 3b which have sulfonated triphenylphosphine ligands, were successfully used under mild conditions as catalysts in reduction reaction of ketones via hydrogen transfer from aqueous 2-propanol, and for hydrogenation of alkynes in aqueous-organic biphasic systems. Graphical Abstract: UF0001